The Effect of Proposed Changes in Salaries and Services of Finance Subdivision Employees on Job Satisfaction of State High School Teachers in Ogan Ilir Regency - Poniton Poniton; Edi Harapan; Heri Setiyo Nugroho (International Journal of Social Science and Humanity, 2025)
This study aims to determine the influence and analyze the proposed changes in salaries and services of financial sub-division employees on the job satisfaction of senior high school teachers in Ogan Ilir Regency, both partially and simultaneously. The population of this study were teachers at senior high schools in Ogan Ilir Regency and the sample taken was 119 teachers. The research data collection technique used questionnaires and documentation. The research data analysis technique used a program assisted by SPSS. The results of this study concluded: 1) The proposed salary changes affect the job satisfaction of senior high school teachers in Ogan Ilir Regency; 2) The services of financial sub-division employees affect the job satisfaction of senior high school teachers in Ogan Ilir Regency; 3) The proposed changes in salaries and services of financial sub-division employees simultaneously affect the job satisfaction of senior high school teachers in Ogan Ilir Regency.